Maisy learns to swim - Cousins, Lucy. (Somerville, Mass. : Candlewick Press, 2013)
Maisy the mouse and her friends take a swimming lesson.
1.8
K-3.
K-3
Keywords: Animals -- Juvenile fiction; Maisy (Fictitious character : Cousins) -- Juvenile fiction; Mice -- Juvenile fiction; Swimming -- Juvenile fiction; Animals -- Fiction; Maisy (Fictitious character : Cousins) -- Fiction; Mice -- Fiction; Swimming -- Fiction; Animals -- Fiction; Maisy (Fictional character : Cousins) -- Fiction; Mice -- Fiction; Swimming -- Fiction; Picture books for children